TEHUNUNA SEBAGAI REPRESENTASI NILAI RELIGIUS DAN SOLIDARITAS SOSIAL MASYARAKAT NEGERI LUHU, SERAM BARAT - Muhammad Junaldi Jufri; Umar Juhfa Samal (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the religious values and social solidarity embedded in the Tehununa tradition practiced by the community of Negeri Luhu, West Seram Regency, Maluku. Tehununa is a cultural tradition performed on the 27th night of Ramadan and plays an important role in the social and religious life of the local community. This research employs a qualitative approach using an ethnographic method to understand the meanings and practices of the tradition within the community’s cultural context. Data were collected through observation, interviews, and documentation. The research informants were selected using purposive sampling, focusing on individuals who possess knowledge and direct involvement in the implementation of the Tehununa tradition. The collected data were analyzed using the interactive data analysis model developed by Matthew B. Miles and A. Michael Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that the Tehununa tradition embodies several religious values, including gratitude to God, spiritual values related to the momentum of Ramadan, values of sharing and charity, and values of togetherness within the community. Furthermore, the tradition also reflects social solidarity that tends toward mechanical solidarity as proposed by Émile Durkheim, characterized by shared beliefs, collective participation, and strong communal ties among members of the community.